Wspólnota poszerzona – spotkania ludzkich i pozaludzkich aktorów - Kowalczyk, Agnieszka (Międzywydziałowa „Pracownia Pytań Granicznych” UAM, 2010)
This paper investigates one of the “posthumanist” propositions of redefining notion of community. It argues that in order to expand community as regards nonhuman animals (Haraway) and technology, things (Latour) it is necessary to go beyond dichotomy of means and ends, instrumental and communicative action.
Expanded community – encounters of human and nonhuman actors
Keywords: ANT; means and ends; nonhuman; Latour; Haraway; laboratory; instrumental action; collective; technology